2020
DOI: 10.1177/1461444820925041
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable populations and misinformation: A mixed-methods approach to underserved older adults’ online information assessment

Abstract: This study examines how low-income African-American older adults, one of the groups most vulnerable to misinformation online, assess the credibility of online information. In examining this, we conducted both face-to-face interviews and a survey and then analyzed how their digital media use, demographics, self-efficacy, and involvement with particular topics were associated with their credibility assessments of online information. Our results suggest that education and topic involvement are statistically signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 50 publications
1
51
1
1
Order By: Relevance
“…Credibility sourcing. During the survey session, an established approach of introducing scenarios of conflicting accounts to assess participants’ strategies for evaluating credibility of information, was used ( Barzilai & Zohar, 2012 ; Seo, Blomberg, Altschwager, & Vu, 2020 ; Thomm et al, 2017 ). Each participant was asked to evaluate two conflicting articles about the COVID-19 pandemic origin in terms of its credibility and trustworthiness.…”
Section: Methodsmentioning
confidence: 99%
“…Credibility sourcing. During the survey session, an established approach of introducing scenarios of conflicting accounts to assess participants’ strategies for evaluating credibility of information, was used ( Barzilai & Zohar, 2012 ; Seo, Blomberg, Altschwager, & Vu, 2020 ; Thomm et al, 2017 ). Each participant was asked to evaluate two conflicting articles about the COVID-19 pandemic origin in terms of its credibility and trustworthiness.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Kruger's study [32] at the University of Hong Kong showed that an experiential learning project of developing undergraduate students' online information assessment skills resulted in a significant increase in the quality of assessment techniques and critical thinking by the students. Similarly, Seo et al [4] found that digital information literacy workshops to older, low-income minority adults in the United States helped them better evaluate health-related information online.…”
Section: Misinformation and Literacymentioning
confidence: 98%
“…Understanding how to enhance citizens' abilities to interpret news and information and evaluate the quality of information has been a key concern of governmental and nongovernmental agencies [4] [7] [13]. Media literacy, information literacy, and digital literacy are the most widely used concepts in this area [14] [15].…”
Section: Media/digital/information Literacy Efforts Around the Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic research based on direct interactions with this population is essential to developing an education program tailored for the women's particular needs and interests. Specifically, a longitudinal technology education model informed by rigorous formative research would help center participants' interests and needs in designing education programs (Seo et al, 2020(Seo et al, , 2019.…”
Section: Policy Implicationsmentioning
confidence: 99%